Pharmaceutical interventions in smoking cessation: systematic review protocol (Research, Society and Development, 2021)
Objective: To describe the methodological steps to carry out a systematic review of pharmaceutical interventions for smoking cessation. Review Method: The protocol for this Systematic Review was developed according to the recommendations of the Prism P guidelines. Will be used as exclusion criteria: comments, editorials, articles that were not in Portuguese, Spanish, and English or articles that were not available in full. Also, articles indexed repeatedly in two or more databases will only be considered once. Two independent reviewers will evaluate titles, abstracts and full texts. Differences in selection will be resolved through a third reviewer. Discussion: This review will aim to critically synthesize the clinical evidence surrounding pharmaceutical interventions for smoking cessation, including data on ethnicity, age, socioeconomic conditions, level of health care, and the intervention environment. Therefore, the use of validated procedures and instruments to assess pharmaceutical interventions in support of smoking patients is essential. Conclusion: This protocol aims to describe the methodological steps to carry out a systematic review of pharmaceutical interventions for smoking cessation, aiming to reduce biases in the search and selection of references, making these criteria clear and uniform among reviewers.